The common γ-chain cytokine receptor: tricks-and-treats for T cells - Waickman, Adam T. (Cell Mol Life Sci, 2015)
Originally identified as the third subunit of the high-affinity IL-2 receptor complex, the common γ-chain (γc) also acts as a non-redundant receptor subunit for a series of other cytokines, collectively known as γc family cytokines. γc plays essential roles in T cell development and differentiation, so that understanding the molecular basis of its signaling and regulation is a critical issue in T cell immunology. Unlike most other cytokine receptors, γc is thought to be constitutively expressed and limited in its function to the assembly of high-affinity cytokine receptors. Surprisingly, recent studies reported a series of findings that unseat γc as a simple housekeeping gene, and unveiled γc as a new regulatory molecule in T cell activation and differentiation. Cytokine-independent binding of γc to other cytokine receptor subunits suggested a pre-association model of γc with proprietary cytokine receptors. Also, identification of a γc splice isoform revealed expression of soluble γc proteins (sγc). sγc directly interacted with surface IL-2Rβ to suppress IL-2 signaling and to promote pro-inflammatory Th17 cell differentiation. As a result, endogenously produced sγc exacerbated autoimmune inflammatory disease, while the removal of endogenous sγc significantly ameliorated disease outcome. These data provide new insights into the role of both membrane and soluble γc in cytokine signaling, and open new venues to interfere and modulate γc signaling during immune activation. These unexpected discoveries further underscore the perspective that γc biology remains largely uncharted territory that invites further exploration.